Pusat Pendidikan Budidaya Padi Di Pekanbaru Dengan Pendekatan Arsitektur Tropis - Rizki Ananda; Wahyu Hidayat; Gun Faisal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The world is faced a crisis on food availability for consumption, it is due to erratic climate condition, the lack of agricultural land, and many farmers choose to plant crops because it is moreprofitable than farming in paddy fields. Rice Cultivation Education Center is a place for teaching, training, research, and recreation on agricultural science, it is about planting and cultivating ricein paddy fields to avoid world food crisis, including in Indonesia. The design uses a method of transformation of concepts and characteristics of tropical architecture that utilizes the deficiency ofthe tropical climate and making it as an excess that can support the function of the building and therefore it contributes to mass formation, mass orientation, the order of landscape, and circulationpatterns inside and outside of the site. The concept of ‘Ruang-Ruang Cahaya’ (spaces of the light) is applied to the design of the building to take advantage of sunlight as energy saving and making it as aesthetic when the light enter the room through the openings. It is applied to the function ofdifferent rooms, an is focused on circulation which connect each room inside the building. The necessity of designing The Rice Cultivation Education Center with Tropical Architecture approachmay provide benefits to the surrounding environment and the activities in the building.Keyword: Rice Cultivation Education Center, Natural Lighting, Tropical Architecture